Local Knowledge on Useful Plants in The Coastal Line Along Parangtritis and its Surroundings - Handayani, Meri; Sulistyowati, Eka (Proceeding International Conference on Science and Engineering, 2020)
In the coastal areas of Parangtritis and its surroundings have plant’s diversity which is still not much researched and documented. Documentation of the useful plants by local people (ethnobotany) is needed so that knowledge will be exist. This is due to the development of technology and science, the local knowledge about plant is increasingly degraded. This study aims to find out the knowledge and use of plants by local people. Data about plant’s diversity was carried out by analyzing vegetation in the coastal areas of Parangtritis and its surroundings which consisted of three locations namely Mangrove Forest of Baros, Parangkusumo Sand Dune, and Karst around Langse Cave. Data collection of ethnobotany was carried out by direct observation and semi-structured interviews with key informants. Snowball sampling technique was used to determine the key informants. The results of the study obtained 40 plant species from 27 families. Among 40 species, there were species that had a single function or others that had multiple function. It divided into 7 usability groups, namely fodder (22 species), medicine (11 species), timber (4 species), household plant (19 species), ritual (2 species), ornamental (6 species), and crafts (2 species).